RESPON FOTOSINTESIS MAKROALGA TERHADAP TEKANAN DESIKASI PADA ZONA INTERTIDAL BERBATU DI DENSHIN HAMA PERAIRAN MURORAN, JEPANG - Mohamad Gazali; Yun Kae Kiang; Masataka Hoashi (JURNAL PERIKANAN TROPIS, 2015)
Dessiccation factors is affecting to photosynthesis response in macroalgae leaf exposed to light of the environment. Hypothesis of this research is macroalgae species scattered in upper zone having high tolerance against dessiccation. This research aims to analyzing macroalgae spesies productivity with using PAM fluorometer. Some species of seaweed was collected like Ulva pertusa, Polyopes affinis, Gloiopeltis furcata, Sargassum thunbergiii and Saccharina japonica. Seawed sampling is based on it dominance in the rocky intertidal zone which includes upper, middle and lower zone. Result of the study show Ulva pertusa less tolerance to dessiccation stress and rarely it can growth in rocky intertidal zone. Nevertheless, species of Polyopes affinis, Gloipertis furcata, Sargassum thunbergii and Saccharina japonica have been gradually increased which it show ability to dessiccation stress from exposure to free air.